Assessment of IASI capability for retrieving carbonyl sulphide (OCS). (November 2017) - Camy-Peyret, C.; Liuzzi, G.; Masiello, G.; Serio, C.; Venafra, S.; Montzka, S.A.
Highlights: Among the first works showing Carbonyl sulphide (OCS) retrievals from IASI. Case study based on two years long record of IASI soundings. Comparison with in situ and airborne OCS observations. Abstract: The capability of IASI (Infrared Atmospheric Sounder Interferometer) for retrieving OCS has been assessed with a series of retrieval experiments, which have been carried out with a physical forward/inverse scheme, which can exploit the full IASI information content. We use random projections to reduce the dimensionality of the data space and to have a unified treatment of instrument and forward model errors. The OCS column amount is retrieved both by using a scaling parameterization of the profile and a non-parametric approach, in which we first derive the OCS profile and then its global amount is estimated by a proper integration over the profile. IASI OCS retrievals are compared to in situ flask observations at the Mauna Loa validation station, Hawaii, USA and observations from HIAPER Pole-to-Pole flights. We have found that the best way to retrieve OCS is through the non-parametric approach, which shows that the OCS cycle amplitude, phase and mean abundance can be retrieved with high accuracy for night and day time soundings. In fact, IASI captures the OCS seasonal cycle, with an overall difference with in situ observations, which is of the order of ≈ 1 pptv, provided we use HITRAN2012 OCS line compilation. HITRAN2008, which has been used in previous studies, is indeed affected by spectroscopic errors as far as OCS is concerned, which results in heavily biased OCS retrievals. Although the present paper is mostly intended to assess IASI retrievals over ocean, a demonstrative application to above land surface is considered as well. Preliminary results suggest that IASI can recover the OCS cycle in ecosystems governed by leaf and/or soil sources/sinks.